Management - Robbins, Stephen P. (Pearson, 2016)
PART 1: Introduction 1. Managers in the Workplace Management History Module 2. Making Decisions Part 1 Management Practice PART 2: Basics of Managing in Today's Workplace 3. Managing the External Environment and the Organization's Culture 4. Managing in a Global Environment 5. Managing Diversity 6. Managing Social Responsibility and Ethics 7. Managing Change and Innovation Part 2 Management Practice PART 3: Planning 8. Planning Work Activities 9. Managing Strategy Creating and Leading Entrepreneurial Ventures Module Part 3 Management Practice PART 4: Organizing 10. Designing Organizational Structure - Basic Designs 11. Designing Organizational Structure - Adaptive Designs 12. Managing Human Resources Managing Your Career Module 13. Creating and Managing Teams Part 4 Management Practice PART 5: Leading 14. Managing Communication 15. Understanding and Managing Individual Behavior 16. Motivating Employees 17. Being an Effective Leader Part 5 Management Practice PART 6: Controlling 18. Monitoring and Controlling Planning and Control Techniques Module Managing Operations Module Part 6 Management Practice